PENGEMASAN BAHAN AJAR TARI MAK INANG PAK MALAU DALAM BENTUK AUDIO VISUAL UNTUK SISWA KELAS X SEKOLAH MENENGAH ATAS - Nanda Pratiwi Hasibuan (Gesture: Jurnal Seni Tari, 2021)
ABSTRACT - This study aims to package the Mak Inang Pak Malau dance learning according to KD 3.1, namely understanding the concepts, techniques, and procedures in imitating the basic movements of dance, in the form of Audio Visual learning media for high school class X students. The theoretical foundation that is used as a guideline in this study is the theory of Arianty et al, (2016: 106), the theory of Rayandra Asyhar (2012: 45) and Sumarno (2011: 23) which explain how the stages or procedures in making audio visual media. The data in this study are in the form of literature and field studies. Literature study is reading references in the form of books, journals / articles and research results. Meanwhile, field data were carried out by means of observation, interviews and documentation. The packaging method uses computer laboratory work. The research method used is descriptive qualitative and quantitative. The results of data processing are arranged systematically in the form of a thesis. The research process or packaging method is carried out in three stages, namely: the first stage of preparation, which is to prepare everything related to research before the shooting process. The second stage of implementation / presentation (production) is the start of the process of shooting or taking videos that will be used as media. The third or final stage is the follow-up, where in this process the media is checked again before it is packaged in the form of a VCD (Video Compact Disc). In this stage, a trial was also held by conducting a material feasibility test and a media feasibility test, making revisions, then being ready for use. This product obtained the results of the feasibility test with a score of 4.77 by the material expert and the results of the due diligence with a score of 4.87 by the media expert. The percentage of eligibility for material experts was 95% and the percentage of eligibility for media experts was 97%. Thus, the results of research on the packaging of the Mak Inang Pak Malau dance in Audio Visual learning media include material understanding concepts, techniques, and procedures for grade X high school students in Medan which are deemed very suitable for use. Keywords: Packaging, Mak Inang Pak Malau Dance, Audio Visual.ABSTRAK - Penelitian ini bertujuan mengemas pembelajaran Tari Mak Inang Pak Malau sesuai KD 3.1 yaitu memahami konsep, teknik, dan prosedur dalam meniru gerak dasar tari, dalam bentuk media pembelajaran Audio Visual untuk siswa kelas X Sekolah Menengah Atas. Landasan teori yang dijadikan pedoman pada penelitian ini adalah teori Arianty dkk, (2016:106), teori  Rayandra Asyhar (2012: 45) beserta Sumarno (2011: 23) yang menjelaskan bagaimana tahapan atau prosedur dalam pembuatan media audio visual. Data dalam penelitian ini berupa studi pustaka dan studi lapangan. Studi pustaka yaitu membaca referensi berupa buku, jurnal/artikel dan hasil penelitian. Sementara data-data lapangan dilakukan dengan cara observasi, wawancara dan dokumentasi. Metode pengemasan menggunakan kerja laboratorium komputer. Metode penelitian yang digunakan yakni deskriptif kualitatif dan kuantitatif. Hasil pengolahan data disusun secara sistematis dalam bentuk skripsi. Proses penelitian atau metode pengemasan dilakukan dalam tiga tahapan yakni: tahapan pertama persiapan, yaitu menyiapkan segala sesuatu yang berkaitan dengan penelitian sebelum proses syuting. Tahapan kedua pelaksanaan/penyajian (produksi) yaitu mulainya proses syuting atau pengambilan video yang akan dijadikan media. Tahap ketiga atau terakhir yaitu Tindak Lanjut, dimana dalam proses ini media dicek kembali sebelum dikemas dalam bentuk VCD (Video Compact Disc). Dalam tahap ini juga diadakan uji coba dengan dilakukannya uji kelayakan materi dan uji kelayakan media, melakukan revisi, kemudian siap digunakan. Produk ini memperoleh hasil uji kelayakan dengan skor 4.77 oleh ahli materi dan hasil uji kelayakan dengan skor 4.87 oleh ahli media. Persentasi kelayakan ahli materi adalah 95% dan persentase kelayakan ahli media adalah 97%. Dengan demikian, hasil penelitian pengemasan pembelajaran Tari Mak Inang Pak Malau dalam media pembelajaran Audio Visual meliputi materi memahami konsep, teknik, dan prosedur untuk siswa kelas X Sekolah Menengah Atas di Medan dinyatakan sangat layak digunakan.  Kata Kunci: Pengemasan, Tari Mak Inang Pak Malau, Audio Visual.